2007
DOI: 10.1055/s-2007-991040
|View full text |Cite
|
Sign up to set email alerts
|

HOX Genes in Implantation

Abstract: Implantation is a complex event requiring synchronization between a developing embryo and receptive endometrium. This process is governed by molecular mechanism mediated by homeobox (Hox) genes, which encode transcription factors. These factors guide embryologic development as well as regulate differential gene expression within the endometrium with each menstrual cycle. Spatiotemporal aberrations in HOX gene expression as seen with polycystic ovarian syndrome, endometriosis, hydrosalpinges, and endocrine disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 49 publications
0
35
0
2
Order By: Relevance
“…Spatiotemporal aberrations in HOX gene expression have been found with polycystic ovarian syndrome (PCOS), endometriosis, hydrosalpinges, and endocrine disrupters that compromise reproduction [8,29]. Moreover, there is accumulating evidence that HOX genes play important roles in oncogenesis, including ovarian cancer progression [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spatiotemporal aberrations in HOX gene expression have been found with polycystic ovarian syndrome (PCOS), endometriosis, hydrosalpinges, and endocrine disrupters that compromise reproduction [8,29]. Moreover, there is accumulating evidence that HOX genes play important roles in oncogenesis, including ovarian cancer progression [30].…”
Section: Discussionmentioning
confidence: 99%
“…We first demonstrated that all three kinds of granulosa cells express HOXA7. Unlike most HOX genes, which are expressed solely during the embryonic period, those specific to the female reproductive tract continue to play a role in the adult [8,31]. The expression of HOXA7 in granulosa cells indicated that HOXA7 exerted a potential role in cell regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. Vitiellе и соавторы указывают, что процесс синхронизации между развитием эмбриона и рецептивным эндометрием регу-лируется молекулярным механизмом, опос-редованным гомеобоксными (НОХ) генами, которые кодируют индукторы транскрипции [10]. Исследователи отмечают, что экспрес-сия генов НОХА 10 и НОХА 11 в эндометрии достигает максимума в «окно имплантации» естественного цикла и напрямую зависит от секреции половых стероидов.…”
Section: молекулярно-генетические индукторы эндометрия в стимулированunclassified
“…Distinct sets of homeobox genes control skeletal patterning, limb formation, craniofacial morphogenesis, development of the central nervous system and other organ systems including the gastrointestinal tract and urogenital organs (Capecchi, 1997;Beck, 2002;Panganiban & Rubenstein, 2002;Christensen et al, 2008). Homeobox genes also control cell renewal and tissue regeneration processes in adults such as hematopoiesis, angiogenesis, spermatogenesis and endometrial remodeling (Gorski & Walsh, 2000;Argiropoulos & Humphries, 2007;Vitiello et al, 2007;Maclean & Wilkinson, 2010).…”
Section: Overview Of Homeobox Genesmentioning
confidence: 99%